Factors Affecting Trust in Chinese Digital Journalism: Approach Based on Folk Theories - Liu, Shaoqiang (2023)
Trust in online digital news has become a significant concern affecting social cohesion in China. Under the framework of folk theories, we interviewed urban and rural residents’ perceptions and imaginations of digital news credibility in China’s digital journalism environment. The study finds that digital media giants in China are utilised by both urban and rural residents. Regarding the behaviour of news avoidance, scepticism of digital news accounts for only a tiny fraction of the reasons held by news avoiders. Chinese urban and rural residents have similar perceptions about the impact of news forms, quality of information, and individual stances on digital news, while rural residents show uncertainty about the transparency of news production, which may be related to their education level and media literacy. The relationship between recommendation algorithms and news trust is overlooked by respondents. In addition, news seekers are more likely to display herd behaviours, which may mislead their judgment of news credibility. News avoiders may refuse to consume news because of their distaste for China’s digital news atmosphere, such as the ubiquity of unpleasant emotions, preconceived opinions, and attention-grabbing clickbait headlines.